ANALISIS PENGARUH CAR, FDR, NPF, BOPO, DAN SIZE TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA (Studi Kasus Pada Bank Umum Syariah di Indonesia Periode 2011-2014) - Wardana, Ridhlo Ilham Putra; Widyarti, Endang Tri (Faculty of Economics and Business Diponegoro University, 2015)
The purpose of this study was to analyze the influence of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), Operating Expenses to Operating Income (BOPO), and Size toward Profitability in Islamic Banks in Indonesia wich were proxied Return on Assets (ROA). The sampling technique used in this study is purposive sampling technique with the criteria of Islamic Banks who publish quarterly financial reports periodically during 2011-2014. The data used in this study was obtained from quarterly financial reports on the website of Islamic Banks with a sample of five Islamic Banks. Methods of data analysis in this study with Multiple Regression Analysis, which previously performed classical assumption test. Hypothesis testing using F-statistic test, t-statistical test and the determination of coefficients Adjusted Â with a significance level of 5%. The results of the study are the independent variables simultaneously (F test) effect on ROA with a significance level of 0.000. While partially (t test) showed that the variable CAR has negative significant effect on ROA. FDR and NPF variables has no significant effect on ROA. While BOPO and Size has significant negative effect on ROA. Adjusted Â is 0.767 which means that the ability of the five independent variables can explain ROA amounted to 76.6%, while the rest is explained by other factors.